Effect of feeding a dried distillers’ grains with solubles diet on the metabolism of the intestinal wall in Guanling crossbred cattle: a preliminary assessment - Luo, Xiaofen; Zhang, Tiantian; Xu, Duhan; Zhu, Mingming; Zhang, Junjie; Zhang, Rong; He, Guangxia; Chen, Ze; Mei, Shihui; Zhou, Bijun; Wang, Kaigong; Chen, Chao; et al. (Frontiers in Veterinary Science, 2024)
Abstract：To investigate effect of feeding dried distiller's grains with solubles (DDGS)-based diets on intestinal metabolites and related pathways in cattle, six Guanling crossbred cattle (Guizhou Guanling Yellow cattle × Simmental cattle) were selected and randomly divided into a basal diet (BD) group and a mixed diet group fed DDGS replacing 25% of dietary concentrates (DDGS) (n=3). Fresh jejunum (J), ileum (I) and cecum (C) tissues were collected for metabolomic analysis. In comparison to the J-BD group, 123 differential metabolites (VIP > 1, p < 0.05) were identified in the J-DDGS group, which (top 20) are mainly divided into super classes, including lipids and lipid-like molecules, organic acids and derivatives and organoheterocyclic compounds. Compared with the I-BD group, 47 differential metabolites were obtained in the I-DDGS group, which are mainly divided into super classes, including lipids and lipid-like molecules and organic acids and derivatives. And the C-DDGS vs C-BD comparison revealed 88 differential metabolites, which are mainly divided into super class, including lipids and lipid-like molecules, organic oxygen compounds, and nucleosides. A total of 34 significantly metabolic pathways were found (p < 0.05, -log(p)>1.3). Among them, 3 significant pathways were significantly enriched in the J-DDGS group, 11 significant pathways were significantly enriched in the I-DDGS group, and 20 significant pathways were significantly enriched in the C-DDGS group. Importantly, primary bile acid biosynthesis, linoleic acid metabolism, and arachidonic acid metabolism correlate with intestinal inflammation and immunity by regulating gut microbiota, prostaglandin synthesis, and cell signaling. The data suggest that DDGS-fed cattle unregulated three metabolic pathways mentioned above and are able to maintain a balance of these three metabolic pathways, thus resulting in improvement of intestinal inflammation and enhanced immunity in cattle. In conclusion, the DDGS diet fed has the potential to improve intestinal inflammation and enhance immunity of Guanling crossbred cattle by regulating the metabolic patterns of Lipids and lipid-like molecules and organic acids and derivatives, and related metabolic pathways.These results allude to potential metabolic regulatory mechanisms of DDGS diets and also provide a theoretical basis for the application of DDGS in livestock feed.